(untitled) (Ustozlar uchun, 2026)
This study presents a comparative analysis of the morphological structures of English and Uzbek languages, focusing on word formation, inflection, derivation, and typological characteristics. English, as an analytic language, and Uzbek, as an agglutinative language, exhibit significant differences in morphological organization. However, both languages share certain universal features in word formation processes. The findings contribute to contrastive linguistics, language teaching, and translation studies by identifying key similarities and differences in morphological systems.